2013
DOI: 10.1002/j.0022-0337.2013.77.1.tb05438.x
|View full text |Cite
|
Sign up to set email alerts
|

AEGD Programs: Why Now, Why More?

Abstract: With an increased number of dental schools graduating more dentists, along with the opening of new dental schools throughout the United States, more graduating dental students are considering utilizing Advanced Education in General Dentistry (AEGD) programs as a means to increase their understanding of the complexity of modern dentistry and to gain additional training and experience before heading into practice. This position paper describes how these programs can aid in transforming the face of dental educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Moreover, with the economic downturn of 2008, financial factors may impact career and practice decisions as the increases in tuition and dental student debt continue to be a concern 2 , 8 . On the other hand, a recent study of residents in advanced education in general dentistry (AEGD) programs found that increasing knowledge and clinical skills was the most important reason for those choosing to enter an AEGD program, while opportunities for student loan deferral and the opportunity to wait for better practice opportunities following U.S. economic recovery had little influence 9 …”
mentioning
confidence: 99%
“…Moreover, with the economic downturn of 2008, financial factors may impact career and practice decisions as the increases in tuition and dental student debt continue to be a concern 2 , 8 . On the other hand, a recent study of residents in advanced education in general dentistry (AEGD) programs found that increasing knowledge and clinical skills was the most important reason for those choosing to enter an AEGD program, while opportunities for student loan deferral and the opportunity to wait for better practice opportunities following U.S. economic recovery had little influence 9 …”
mentioning
confidence: 99%
“…This method of training may subject patients to discomfort, risk of complications, and prolonged procedure times 2 . At the same time, there may be limited access to more complex cases with corresponding difficulty in training in a time‐effective manner 3 …”
mentioning
confidence: 99%